2010
DOI: 10.3945/jn.109.119636
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Serum 25-Hydroxyvitamin D Concentrations Are Associated with Small-for-Gestational Age Births in White Women

Abstract: Maternal vitamin D deficiency has been associated with numerous adverse health outcomes, but its association with fetal growth restriction remains uncertain. We sought to elucidate the association between maternal serum 25-hydroxyvitamin D [25(OH)D] concentrations in early pregnancy and the risk of small-for-gestational age birth (SGA) and explore the association between maternal single nucleotide polymorphisms (SNP) in the vitamin D receptor (VDR) gene and the risk of SGA. We conducted a nested case-control s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
220
1
16

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 258 publications
(255 citation statements)
references
References 62 publications
18
220
1
16
Order By: Relevance
“…This study reported a decrease in the inflammatory response with vitamin D treatment by measurement of IL-8 [24]. Also of note, vitamin D has been associated with increased risk of preeclampsia [25], infants that are small for gestational age (SGA) [26][27][28][29], cesarean section [30], and gestational diabetes (GDM) [31].…”
Section: Pregnancy Lossmentioning
confidence: 72%
“…This study reported a decrease in the inflammatory response with vitamin D treatment by measurement of IL-8 [24]. Also of note, vitamin D has been associated with increased risk of preeclampsia [25], infants that are small for gestational age (SGA) [26][27][28][29], cesarean section [30], and gestational diabetes (GDM) [31].…”
Section: Pregnancy Lossmentioning
confidence: 72%
“…A nested case-control study of seventy seven mothers who had their serum 25-OHD concentrations determined at 22 weeks gestation reported a significant association with both low (< 37 . 5 nmol/l) and high (> 75 nmol/l) maternal 25-OHD concentrations and the incidence of SGA (21) (Fig. 2).…”
Section: Effects Of Maternal Vitamin D Deficiency On Fetal Growth Andmentioning
confidence: 92%
“…This does not exclude a potential contribution of vitamin D to GDM risk, but also raises the possibility of other pertinent seasonal factors. (26) Schneuer et al (27) Bodnar et al (28) Flood-Nichols et al (20) Akcakus et al * ng/ml has been converted to nmol/l for the purpose of comparison.…”
Section: Discussionmentioning
confidence: 99%
“…For example, because vitamin D increases intestinal absorption of Ca, in a population where dietary calcium is particularly low, vitamin D status maybe an important predictor for developing pre-eclampsia but not when dietary Ca is adequate (30) . Genetic polymorphisms of the vitamin D nuclear receptor and vitamin D binding protein have been associated with a wide variety of conditions (33,34) , and may explain why a study in the USA found that vitamin D deficiency (<37·5 nmol/l) was a risk factor for SGA in white women (adjusted OR 7·5; 95 % CI 1·8, 31·9) but not in black women (adjusted OR 1·5; 95 % CI 0·6, 3·5) (28) . This study found a non-linear association between 25-hydroxyvitamin D concentration and SGA, with an increased risk of SGA with concentrations >75 nmol/l (OR 2·2; 95 % CI 1·2, 3·8).…”
mentioning
confidence: 99%